Analisis Hukum Terkait Perbuatan Melawan Hukum Dalam Perjanjian Sewa Menyewa Yang Menyebabkan Kerugian (Studi Kasus Putusan Mahkamah Agung Nomor 2925 K/Pdt/2019) - William Jason; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2024)
One of the legal acts in the agreement is leasing, which is regulated in Articles 1548 to 1600 of the Civil Code. In Article 1548 of the Civil Code, leasing is defined as an agreement, by which one party binds himself to give the enjoyment of an item to the other party during a certain time, with the payment of a price agreed by the latter party. People can lease various types of goods, both fixed and movable. Sometimes a lease agreement often raises various legal issues, such as default or breach of promise or unlawful acts. Unlawful acts in a lease agreement can be interpreted as a negligent act or any act that violates agreed rights and/or obligations and is contrary to applicable laws and regulations, causing material or immaterial losses to others. This research is intended to analyze the legal consequences arising from unlawful acts committed by the renting party through Supreme Court Decision Number 2925 K/Pdt/2019. By using a normative juridical approach, the results of this study show that the actions of the subletting party can be categorized as unlawful acts because it terminates the lease agreement unilaterally, while there is still a validity period of the lease to which the tenant is entitled. This caused the tenant to be materially and materially disadvantaged, so they sued until the cassation level.